1974
DOI: 10.1677/joe.0.0600205
|View full text |Cite
|
Sign up to set email alerts
|

Oestrogen and Progesterone Influence on the Release of Prolactin in Ovariectomized Rats

Abstract: SUMMARY The concentration of prolactin in serum after oestrogen and progesterone injection into spayed rats was measured by radioimmunoassay. After a single injection of 5 μg oestradiol benzoate (OB) into long-term ovariectomized rats, serum prolactin concentrations showed a circadian rhythm with high levels in the afternoon and almost no changes in the morning. Peaks of prolactin occurred 2, 3 and 4 days after the injection. Below a dose of 1 μg OB, the response was dose-dependent, but the response was then m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
58
2

Year Published

1978
1978
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(68 citation statements)
references
References 0 publications
8
58
2
Order By: Relevance
“…Estradiol treatment in ovariectomized (OVX) rats induces daily PRL surges that occur at roughly the same time of day as the proestrous surge (13). Shifting of the light phase results in a coincident shift of the proestrous surge (10), and the estradiol-induced PRL surges of OVX rats free run in constant light (52), but the mechanism regulating the circadian profile of PRL secretion is still unknown.…”
mentioning
confidence: 99%
“…Estradiol treatment in ovariectomized (OVX) rats induces daily PRL surges that occur at roughly the same time of day as the proestrous surge (13). Shifting of the light phase results in a coincident shift of the proestrous surge (10), and the estradiol-induced PRL surges of OVX rats free run in constant light (52), but the mechanism regulating the circadian profile of PRL secretion is still unknown.…”
mentioning
confidence: 99%
“…This increase in L TH can be due to increase in progesterone levels in the blood, which stimulates the release of prolactin as Caligaris et al (1974) found in the rat. The increase in the amount of LTH at this period could prove that corpora lutea in rabbits depend in addition to other physiological activities on prolactin.…”
Section: Discussionmentioning
confidence: 73%
“…Most studies on the hormonal regulation of prolactin (PRL) release have focused on the role of the ovarian steroids (Freeman et al 1972, Caligaris et al 1974, Arbogast & Ben Jonathan 1990. However, accumulated evidence indicates that the adrenal gland is also able to regulate PRL secretion (Brann et al 1990.…”
Section: Introductionmentioning
confidence: 99%